Bacterial compounds, as biocontrol agent against early blight (Alternaria solani) and tobacco cut worm (Spodoptera litura Fab.) of tomato (Lycopersicon esculentum Mill.). (27th August 2018) - Chanthini, Kanagaraj Muthu-Pandian; Senthil-Nathan, Sengottayan; Soranam, Ramaiah; Thanigaivel, Annamalai; Karthi, Sengodan; Sreenath Kumar, Chinnadurai; Kingsley, Samuel Jayasurya; Kanagaraj Murali-Baskaran, Ramasamy
Abstract: Tomato, the important vegetable crop faces yield loses by foliar disease, Early Blight caused by Alternaria solani and infestation by tobacco cut worm, Spodoptera litura . Synthetic pesticides used for disease and pest control resulted in environmental pollution as well as development of resistance. By way of a need to develop a new biopesticide, bacteria were tested for their anti-fungal and insecticidal activity. Volatile compounds and peptides from the bacteria, Bacillus subtilis, Staphylococcus aureus and Pseudomonas aeruginosa were able to inhibit the hyphal growth and melanin production of A. solani . S. aureus showed the highest inhibitory effect as well as reduced the disease severity. B. subtilis exhibited the highest mortality rate of 87% and 83% against I and II instar of S. litura, respectively. The bacteria offered effective biocontrol at 35 °C. Bioactive substances from the bacteria can be used as potential biocontrol agents against the pest and disease of tomato.